Investigation of Primary School Teacher Readiness in Online Learning during the Covid-19 Pandemic - Wahyuni, Esa Nur; Aziz, Rahmat; Wargadinata, Wildana; Efiyanti, Alfiana Yuli (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2021)
Changing the learning system during the pandemic period from offline to online requires teachers' readiness, including elementary school teachers. Demands for mastery of technology in learning and the characteristics of elementary school students who need direct guidance in learning are teachers' problems. However, not all primary school teachers are ready for technology-based online learning. This study aims to investigate the readiness of primary school teachers in online learning in terms of three aspects, namely cognitive (knowledge and perception), affective (emotional condition), and moral (skills). The research method uses a mixed-method with data collection techniques using a questionnaire deepened by interviews. The research respondents were 22 elementary school teachers in Tlekung village, Junrejo district, Batu City. Data analysis used descriptive statistical analysis and qualitative analysis. The results showed that the teacher had a low readiness to carry out online learning in general. The level of primary school teachers' readiness to carry out online learning still needs to be improved, especially in the knowledge and skills factor by providing online learning training experiences.